Relationship Between Emotional Intelligence and Occupational Stress Levels Among Certified Registered Nurse Anesthetists. - Bittinger, Andrea C. (AANA Journal, 2020)
Certified Registered Nurse Anesthetists (CRNAs) are exposed to multiple job-related stressors and therefore experience high levels of occupational stress and job burnout. In healthcare systems, job burnout from occupational stress may lead to poor patient care and safety outcomes. Prior research findings suggest nurses who reported higher levels of emotional intelligence (EI) had significantly lower work-related stress and less job burnout than nurses who reported lower levels of EI. To date, the relationship between EI and occupational stress among CRNAs has not been studied. The purpose of this study was to determine if a relationship exists between EI levels and workplace stress levels among CRNAs. A descriptive survey design was used to answer the research question. Findings from the study reveal a significant relationship between the levels of EI and levels of stress in the CRNA population surveyed (r = -0.20, P = .01). CRNAs who reported higher levels of EI experienced less workplace stress than CRNAs who reported lower levels of EI. Additional findings suggest that CRNAs who have higher levels of EI are better able to cope with occupational stressors. Developing and implementing strategies to increase EI among CRNAs may be key to decreasing work-related stress and burnout.